CARBON STOCK ANALYSIS IN THE FOREST STANDS OF MOUNT PESAGI PROTECTED FOREST, WEST LAMPUNG - surnayanti surnayanti; Komang Intan Gayatri; Ceng Asmarahman (Universitas Muhammadiyah Palembang, 2026)
Climate change driven by increasing greenhouse gas emissions, particularly carbon dioxide (CO?), has caused atmospheric energy imbalance, leading to global warming and ecological disruption. Forest ecosystems play a vital role as carbon sinks by storing carbon in biomass and soil. This study aimed to estimate carbon stock in forest stands and ecosystem components of the Mount Pesagi Protected Forest, West Lampung. The research was conducted from February to July 2025 using a quantitative descriptive approach. Data were collected through direct field measurements of living biomass (trees, poles, saplings, and understory vegetation) and dead biomass (litter and necromass) across purposively selected plots. The results identified 12 tree species from 10 families, dominated by Fagaceae, Lauraceae, and Dipterocarpaceae. The total ecosystem carbon stock was 314.16 tons/ha, primarily contributed by soil carbon (285.00 tons/ha; 90.8%), followed by necromass (13.06 tons/ha; 4.1%), living biomass (11.33 tons/ha; 3.6%), and surface organic matter (4.77 tons/ha; 1.5%). These findings indicate that the forest functions as a significant carbon pool in tropical montane ecosystems. Overall, the Mount Pesagi Protected Forest plays an important role in biodiversity conservation and long-term carbon sequestration, contributing to climate change mitigation and sustainable forest management.